2014
DOI: 10.1007/s12282-013-0512-0
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral heterogeneity of the distribution of kinetic parameters in breast cancer: comparison based on the molecular subtypes of invasive breast cancer

Abstract: Each molecular subtype of invasive breast cancer showed a heterogeneous kinetic pattern in dynamic-contrast magnetic resonance imaging (MRI). The HR+/HER2- cancers and the TN cancers had relatively lower percentages of washout pattern. When a manual assessment of the kinetic parameters is performed, close attention should be paid in order to identify the malignant washout kinetic pattern, particularly in HR+/HER2- cancer and TN cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 31 publications
1
62
0
1
Order By: Relevance
“…There are several studies 19,20,24,29,30 in the literature that have related breast MRI kinetics to cancer subtype. Bhooshan et al 19,20 studied 353 MRI cases and correlated breast MRI radiomics features to non-invasive and invasive cancer types.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several studies 19,20,24,29,30 in the literature that have related breast MRI kinetics to cancer subtype. Bhooshan et al 19,20 studied 353 MRI cases and correlated breast MRI radiomics features to non-invasive and invasive cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Mazurowski et al 24 performed radiogenomic analysis on a subset of 48 cases from TCIA to determine whether enhancement dynamics could predict the luminal B subtype. A study by Yamaguchi et al 29 investigated the connection between kinetic curve pattern and molecular subtypes. Blaschke et al 30 reported that HER2-enriched tumors have a larger volume of rapid early uptake compared with other molecular types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings contribute to a range of recently elucidated quantitative markers that together define imaging phenotypes that have shown promise in the identification of additional cancer subtypes, lesion invasiveness, grade, and lymph node status, with associated treatment and prognostic implications. [5][6][7][8][9][10][11][18][19][20] Classification of breast cancer by molecular subtype furthermore has clinical value, as current treatment guidelines are determined by tumor subtype. 16 HER2 expression by cancers in particular needs to be determined, as anti-HER2 therapy has well documented efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The election imaging method for Breast Cancer (BC) was MRI (78%) [91,97,103,104,105,106,107,108,109,110,111,112,113,114,115,116,120,121]. About 78% of the BC published papers were correlation studies [91,103,104,105,106,107,108,109,110,111,112,114,117,118,119,120,122,123] and the most used genomic data was IHC results (65%) [103,104,105,107,108,111,112,113,114,115,116,117,118,119,120].…”
Section: Discussionmentioning
confidence: 99%